Mathematical model of a closed-loop oscillating heat pipe with check valves - Wannapakhe, S.; Rittidech, S. (Journal for Developing the Social and Community, 2014)
The heat transfer characteristics of a closed-looped oscillating heat pipe with check valves (CLOHP/CV) were modeled using the explicit finite element method. The parameters affecting the heat transfer of a CLOHP/CV were analytically investigated. The principles and theories of basic governing equations and a finite difference scheme were applied to evaluate the heat transfer rate. The predicted heat transfer rate, obtained from the model, was compared to the existing experimental data. The effect of evaporator length, inner diameter and working fluid on the performance of a CLOHP/CV were also investigated.